Comparison of Pretectal Genoarchitectonic Pattern between Quail and Chicken Embryos - Merchán, Paloma; Bardet, Sylvia M.; Puelles, Luis; Ferran, José L. (Frontiers in Neuroanatomy, 2011)
Regionalization of the central nervous system is controlled by local networks of transcription factors that establish and maintain the identities of neuroepithelial progenitor areas and their neuronal derivatives. The conserved cerebral Bauplan of vertebrates must result essentially from conserved patterns of developmentally expressed transcription factors. We have previously produced detailed molecular maps for the alar plate of prosomere 1 (the pretectal region) in chicken (Ferran et al., 2007, 2008, 2009). Here we compare the early molecular signature of the pretectum of two closely related avian species of the family Phasianidae, Coturnix japonica (Japanese quail) and Gallus gallus (chicken), aiming to test conservation of the described pattern at a microevolutionary level. We studied the developmental pretectal expression of Bhlhb4, Dbx1, Ebf1, Gata3, Gbx2, Lim1, Meis1, Meis2 Pax3, Pax6, Six3, Tal2, and Tcf7l2 (Tcf4) mRNA, using in situ hybridization, and PAX7 immunohistochemistry. The genoarchitectonic profile of individual pretectal domains and strata was produced, using comparable section planes. Remarkable conservation of the combinatorial genoarchitectonic code was observed, fundamented in a tripartite anteroposterior subdivision. However, we found that at corresponding developmental stages the pretectal region of G. gallus was approximately 30% larger than that of C. japonica, but seemed relatively less mature. Altogether, our results on a conserved genoarchitectonic pattern highlight the importance of early developmental gene networks that causally underlie the production of homologous derivatives in these two evolutionarily closely-related species. The shared patterns probably apply to sauropsids in general, as well as to more distantly related vertebrate species.